\(a+\sqrt{1-a^2}=b+\sqrt{1-b^2}\)
\(\Rightarrow a\sqrt{1-a^2}=b\sqrt{1-b^2}\) (bình phương 2 vế và rút gọn)
\(\Rightarrow a^2\left(1-a^2\right)=b^2\left(1-b^2\right)\)
\(\Rightarrow a^4-b^4-\left(a^2-b^2\right)=0\)
\(\Rightarrow\left(a^2-b^2\right)\left(a^2+b^2\right)-\left(a^2-b^2\right)=0\)
\(\Rightarrow\left(a^2-b^2\right)\left(a^2+b^2-1\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}a^2+b^2=1\\a=b\end{matrix}\right.\) \(\Rightarrow\left[{}\begin{matrix}a^2+b^2=1\\a^2+b^2=2a^2=2b^2\end{matrix}\right.\)
Có 2 trường hợp xảy ra, chắc bạn ghi thiếu điều kiện \(a\ne b\) để loại trường hợp dưới ko ra số cụ thể.